Pengaruh Pertimbangan Pasar Kerja, Penghargaan Finansial Dan Nilai-Nilai Sosial Terhadap Minat Menjadi Akuntan Publik - Gloria, Dania; Asliana, Endang; Dewi, Dian Nirmala (Jurnal Akuntansi & Keuangan Unja, 2025)
This study aims to analyze the influence of job market considerations, financial rewards, and social values on the interest of accounting students to pursue a career as public accountants at state universities in Bandar Lampung City. This research uses a quantitative approach with a survey technique through questionnaires distributed to 100 accounting students who have taken or are currently taking professional and business ethics courses. The sampling technique applied is purposive sampling and the data were processed using SPSS version 26. The results show that job market considerations and financial rewards do not affect students’ interest in becoming public accountants, while social values have a positive influence on their interest in pursuing this profession. These findings are expected to provide input for educational institutions and the Indonesian Institute of Accountants (IAI) in formulating strategies to improve the image of the public accounting profession and to help students make more mature career choices in line with job market opportunities and the social values that develop in society.